PELAKSANAAN PEMBELAJARAN SENTRA BERMAIN PERAN DALAM MENGEMBANGKAN KEMAMPUAN BERBICARA ANAK USIA 4-5 TAHUN - Wasitoh Nuri; Isti Rusdiyani; Tri Sayekti (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2019)
The ability to speak has a very important in the child’s life because the ability to speak children is easy to socialize with friends and the environment. This research are design to describe how the implementation of learning in role playing centers develops the speaking ability of children aged 4-5 years at the Widya Cendekia Islamic Kindergarten in Serang City. This study uses a descriptive research method with a qualitative approach. The subjects in this study were children aged 4-5 years totaling 24 children. Techniques for collecting data through observation, field notes, interviews and documentation. Data analysis using data reduction, data presentation and conclusions. Validation is done by extending observations, increasing research perseverance, triangulation and checking members. The results of the data analysis stated that: 1) speaking ability of children aged 4-5 years in the Widya Cendekia Islamic Kindergarten in Serang City developed well; 2) the implementation of learning role playing centers at the Widya Cendekia Islamic Kindergarten in Serang City capable of developing children’s speaking skills; 3) Learning media for role playing centers in the Widya Cendekia Islamic Kindergarten in Serang City are able to meet the needs of children in developing speech skills; 4) supporting and inhibiting factors the implementation of learning center role playing in TK Islam Widya Cendekia. Supporting factors are: 1) teacher center who masters learning material; 2) child self-motivation; and 3) infrastructure facilities or supporting media tools. Inhibiting factors are emotions or mood of children who are not good or easily change.